Investigating the load, friction and sealability characteristics of graphite valve packings - Ní Ruaidhe, Máire (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2005)
It is widely accepted that valve stem leakage accounts for the majority of fugitive emissions from petrochemical and chemical sites often accounting for over 50% of fugitive emissions from these sites. The most common valve sealing device is the compression packing and even though compression packings have been used for over 150 years, there is still a considerable lack of knowledge into how they effect a seal in a valve. This project hopes to bridge this gap by gaining a greater scicntific understanding of their behaviour in order to implement improvements in compression packing installation and operation.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin